Near-IR Transillumination and Reflectance Imaging at 1,300 nm and 1,500–1,700nm for In Vivo Caries Detection - Simon, Jacob C (Lasers Surg Med, 2016)
INTRODUCTION: Several studies suggest that near-IR imaging methods at wavelengths longer than 1,300nm have great potential for caries detection. In this study, the diagnostic performance of both near-IR transillumination and near-IR reflectance was assessed on teeth scheduled for extraction due to orthodontic treatment (n = 109 teeth on 40 test subjects). METHODS: Three intra-oral near-IR imaging probes were fabricated for the acquisition of in vivo images using a high definition InGaAs camera and near-IR broadband light sources. Two transillumination probes provided occlusal and approximal images using 1,300nm light which manifests the highest transparency in enamel. A third reflectance probe utilized cross-polarization and operated at wavelengths greater than 1,500nm where water absorption is higher which reduces the reflectivity of sound tissues, significantly increasing lesion contrast. Teeth were collected after extraction and sectioned and examined with polarized light microscopy and microradiography which served as the gold standard. In addition, radiographs were taken of the teeth and the diagnostic performance of near-IR imaging was compared with radiography. RESULTS: Near-IR imaging was significantly more sensitive (P < 0.05) than radiography for the detection of lesions on both occlusal and proximal surfaces. CONCLUSION: Near-IR imaging methods are ideally suited for screening all tooth surfaces for carious lesions.